Emergence of Communal Politics In India: Understanding the Influence of Communal Politics on Colonial India (Journal of Advances and Scholarly Researches in Allied Education, 2014)
Animportant feature of colonial India was the emergence of communalism as a forcethat guided the destiny of India into a blood bath and inevitable partition ofthe Indian subcontinent on communal lines. Though India was a land ofmulti-religions, creeds and faiths, pre-colonial India was never plagued by theworm of communalism.